Landscape histories: Origin narratives and toponyms in the rural commune of Liboré, Niger - Sandra Bornand; Lawali Dambo (Tydskrif vir letterkunde, 2025)
In this article, we investigate how migration narratives, village founding stories, and place names shape the landscape and spatial memory of Liboré, a rural commune now located on the peri-urban near Niger’s capital. Drawing on fieldwork and an interactive map, we explore how these forms of oral discourse reflect and produce processes of anthropisation (physical transformation of the environment) and humanisation (the assignment of meaning and value to places). Migration stories recount the symbolic and practical logic of settlement, while founding narratives describe how hostile environments—dense bush, spirits, floods, or drought—are made liveable through clearing, adaptation, and negotiation with non-human forces. These stories embed crisis, displacement, and resilience into collective memory. Toponyms act as micro-narratives that capture environmental features, historical traumas, and social structures. Some commemorate ancestors or ecological traits; others encode memories of slavery, forced labour, or colonial extraction. Place-naming emerges as a performative act that reconfigures relationships to land and power. By weaving together narrative and spatial analysis, we show how the communities of Liboré continuously reshape their territory through stories, names, and memories. These practices not only document transformation—they enact it, revealing how naming and narratives are central to processes of territorial claim, identity formation, and environmental perception.